The Impact of Online Gaming Addiction On Behavior Change Among Adolescents - Andi Sri Purnama Danianti; Tenriwati; Amirullah (Jurnal Life Birth, 2021)
Online game addiction is a bad habit that can damage the health of ourselves and others, dependence on online games will attack our vision if overused and can also affect our behavior. This habit does not only occur in adults but has spread to adolescents and even elementary school students. The purpose of this study is to know online game addiction to behavior change among adolescents at SMPN 1 Bulukumba in 2020. This research uses quantitative methods. The research subjects were 32 respondents who were selected using purposive sampling in data collection, the researcher used a questionnaire and an interview late. The analysis in this study used Analytical Observational and this study used the Chi-Square test. The results of the analysis used the Chi-Square test statistical test with a value (Î± = 0.05). Based on the results of this test, the value of Ï is 0.005, thus Ï <Î± (0.005 <0.05), so Ho is rejected and Ha is accepted. The conclusion of this study is that there is a relationship between online game addiction on behavior change among adolescents at SMPN 1 Bulukumba in 2020. Researchers suggest that the results of this study can be used as a reference.